A importância das escalas espaciais e temporais para a avaliação do paradoxo da invasão. - Santos, Daniel Alves dos (2016)
The invasion paradox consists of two possibilities: biotic acceptance, which is a positive association between native and nonnative species in large spatial scales, and the biotic resistance, negative association often found in smaller spatial scales. The paradox is also based on the assumptions that environments with lower species richness have lower resistance against establishment of invasive species, and vice versa. In order to test the paradox, three different spatial scales were selected because their geographical localization, exposed to the same climatic factors and the same regional dynamics, monitored by a long-term ecological research. The selected environments enabled the analysis of invasion paradox in a spatial gradient focusing on a Neotropical aquatic environment. There was no evidence of biotic resistance, so, we observed a paradigm shift regarding the generalization of the paradox concept in biological invasions. The paradox was not confirmed by the absence of alteration in the pattern of relations, i.e., every relation between native and nonnative species were positive, regardless of the spatial scale. The result presented to be contrary to the expected and known in literature, where it argues that biotic acceptance is related to broader scales, while biotic resistance is to smaller ones. Due to this result, subsequently, we sought to integrate the use of the functional characteristics of the species, however, subjected to an assessment in a temporal scale. The patterns shown by functional richness measures (Fric) represented by groups of native and nonnative, showed similar tendencies in relation to the temporal scale, and for the functional diversity measurement (FD) was found that the distance expected between groups (native and native/nonnative combined) over time was not evident. Both groups of species (native and nonnative), were driven by environmental filters and responded similarly to regional variations over time. Considering the biotic acceptance assumption found for this area, we conclude that nonnative species already have established in the region, mainly due to functional similarities presented with native species.